Waiting on a spirit of promise life and theology of suffering of Abraham Cheare - Hanson, Brian L.; Haykin, Michael A. G. (Cambridge : James Clarke, 2014)
Waiting on the Spirit of Promise'' is a study of the life and ministry of Abraham Cheare (1626-1668), containing selections from Cheare's works, and rescuing an important seventeenth-century English Baptist from obscurity. Cheare has been overshadowed by other more celebrated Baptist contemporaries, but as the pastor of the Particular Baptist work in Plymouth, Devon, Cheare played a key role in the advance of the Baptist cause in the West Country in the 1650s. His ''Sighs for Sion'' is an excellent illustration of early Baptist piety. With the Restoration of the monarchy in 1660, Cheare, like.
Front Cover; Title Page; Copyright information; Contents; Introduction; 1. Sweet for Jesus' Sake: The Life of Abraham Cheare; 2. Lift up Our Voice Like a Trumpet: Cheare's Ministry in the 1650s; 3. Waiting on the Spirit of Promise: Abraham Cheare in Prison in the 1660s; 4. A Letter of Abraham Cheare on Baptism, c. 1648-1658; 5. Abraham Cheare, Sighs for Sion; 6. Abraham Cheare, A Looking-Glass; 7. Abraham Cheare, Words in Season; Letters; Bibliography; Back Cover.
CIP data; item not viewed.
Master record variable field(s) change: 072
Keywords: Cheare, Abraham, -- -1668.; Puritan movements -- England -- History -- 17th century; Suffering -- Religious aspects -- Church of England; Cheare, Abraham, -1668.; Suffering -- Religious aspects -- Christianity; RELIGION -- Christianity -- Presbyterian; BIOGRAPHY & AUTOBIOGRAPHY / Religious; Electronic books